UMP pays tribute to the Malay language - UMP, PNC
In its efforts to glorify the Malay language, Universiti Malaysia Pahang (UMP) introduced a Malay language programme for international students (BMfIS) so they could learn and understand better the subject, its history, arts as well as the life style of Malaysians.